Importancia del plan de riesgos ante posibles desastres naturales en la Unidad Educativa Victoria Vasconez Cuvi en el bloque norte en el periodo lectivo 2015-2016 - Chicaiza Chuquitarco, María Elena (2017)
This research was aimed to diagnose the importance of natural disaster risk reduction plan. Topic of relevance in all the unit educational for the eventualities that have happened. By what is significant that them teaching are trained and updated about how act before some event is by this that need of a manual operating safe and with contained responsible this will facilitate how must act it community educational allowing so prepare is for Act and facilitate a recovery more fast in it unit educational, was important identify articles scientific which helped to get themes on them disasters natural that can happen in the institution taking in has all the information that is obtained for said project were instruments that were made, which were the teacher survey and interview the Coordinator of the Committee of management of risks and thus analyzed collected data....